2022
DOI: 10.3390/agronomy12020243
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Animal Manures on Nutrient Recovery and Soil Quality in Acid Typic Hapludalf under No-Till Conditions

Abstract: No-till farming and manure application are means of storing carbon in soil and increasing soil quality. However, the organic fertilization of no-till soils may sustain subtropical agroecosystems for only a limited period until the soil quality declines. The C, N, P, and other nutrient cycles are perturbed due to the nutrient imbalance in manures and their application on the soil surface, which poses a risk for nutrient dispersion into the environment. Long-term N-based manure application also impacts the appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 105 publications
(137 reference statements)
1
19
1
Order By: Relevance
“…In contrast to the mineral fertilizers, dairy slurry supplies simultaneously several nutrients ( Table 5 ) that can contribute to the increased crop yield. However, unlike what is reported in long-term experiments [ 46 , 59 ], our results showed that there were no significant differences in soil P, K, Ca, Mg and Na levels between mineral fertilizer and dairy slurry-based treatments. As P and K inputs were levelled among the treatments, the absence of differences was already expected.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the mineral fertilizers, dairy slurry supplies simultaneously several nutrients ( Table 5 ) that can contribute to the increased crop yield. However, unlike what is reported in long-term experiments [ 46 , 59 ], our results showed that there were no significant differences in soil P, K, Ca, Mg and Na levels between mineral fertilizer and dairy slurry-based treatments. As P and K inputs were levelled among the treatments, the absence of differences was already expected.…”
Section: Discussioncontrasting
confidence: 99%
“…Among the strategies evaluated, ADS was the one that presented the ANR values closest to MB, MS and IN, thus showing its potential to replace them when applied to stubble-covered soils, without incorporation into the soil. Greater nutrient use efficiency is commonly related to the greater nutrient availability in the soil and at the same time, to the lower nutrient losses such as gas emissions and leachate [ 45 , 46 ]. MS, MB, ADS and IN led to the highest values of N-ANR, significantly superior to RDS T16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pig slurry and pig deep litter (swine manure and rice husk), tested with other organic and mineral fertilizers, in a long experiment (2004−2020), led to an increase in soil pH by up to one unit, increasing the C content of the soil, and the level of mineral elements in the soil (P, K, Ca, Mg) [45].…”
Section: Discussionmentioning
confidence: 99%
“…The result conforms with Asfaw (2022) [4] who reported that poultry manure unlike chemicals and other organic fertilizers, added organic matter to the soil which improved soil composition, nutrient retention, aeration, soil moisture-holding capacity, and water infiltration. Also, Ferreira, Ceretta, Lourenzi, De-Conti, Marchezan, Girotto, et al, (2022) [5] opined that animal manure significantly increases soil moisture, as well as soil compaction, which results to increase in soil moisture and water retention capacity. On the other hand, the amount of fertilizer used was positive and statistically significant at 1% level, which agrees with the "apriori" expectation.…”
Section: Determinants Of Output In Maize Production In the Study Areamentioning
confidence: 99%